Gaelscoil alumni who studied languages at third level: Does attending a Gaelscoil impact ability to acquire an additional language and attitude towards language learning? - Owens, Sarah (Marino Institute of Education, 2022)
Previous research suggests that there is a positive correlation between bilingualism and additional language acquisition. While studies have addressed Gaelscoileanna and additional language acquisition separately, the researcher believes that the connection between these two fields has not yet been fully developed or rendered explicit. The purpose of this research was to explore the extent to which attending a Gaelscoil impacts ability to acquire an additional language and attitude towards language learning. The author of this study was curious to ascertain if being a past pupil of a Gaelscoil influences one’s decision to study languages at third level. A small-scale qualitative study was undertaken, positioning itself within the interpretive worldview. Eight Gaelscoil alumni who studied languages at third level were interviewed and their experiences of early immersion in the Irish language and additional language acquisition are described in rich verbal reports. This research revealed that there are a number of elements at play which influence ability to acquire an additional language and attitude towards language learning. These include the advantages of bilingualism, the ease of acquiring an additional language, the role of parents in influencing motivation to learn languages, attitude towards the Irish language, language and culture, and early immersion in the Irish language. Furthermore, the findings shed light on improving practice when promoting cultural and language awareness through the implementation of the Primary Language Curriculum. Several recommendations are put forth for future research related to the nexus between Irish medium education and additional language acquisition, such as gender and language learning, DEIS Gaelscoileanna, curriculum reform, policy, pedagogical practice, the 20-Year Strategy for the Irish Language 2010–2030, and international relevance. It is the researcher’s hope that this study may contribute to developing further knowledge surrounding the benefits of immersing children in a second language at an early age. The author of this study believes this will positively impact ability to acquire additional languages and attitude towards language learning throughout life.
Keywords: Education, bilingual; Gaeilscoil; Qualitative research; Language and languages--Acquisition; Motivation in education; Primary Language Curriculum; Immersion technique (Education); Semi-structured interviews; Education, bilingual; Qualitative research; Language and languages--Acquisition; Motivation in education; Immersion technique (Education); Semi-structured interviews